2013
DOI: 10.3109/09537104.2013.786822
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in chronic urticaria and its correlation with disease severity

Abstract: Chronic urticaria (CU) is characterized by the occurrence of wheals lasting for more than 6 weeks. The role of platelet activation in the pathophysiology of this condition has not been clearly studied. We undertook a cross-sectional study among 45 patients with CU and 45 age- and gender-matched healthy controls. The severity of the disease was assessed using the urticaria severity score. The autologous plasma skin test (APST) was done in all cases of CU. The platelet count and indices were estimated by an auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 16 publications
7
48
1
1
Order By: Relevance
“…In addition, no correlation was observed between MPV and erythrocyte sedimentation rate (ESR), Increased MPV has been reported in adults with CSU (11,18,20). Consistent with the literature, we also found high MPV value in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, no correlation was observed between MPV and erythrocyte sedimentation rate (ESR), Increased MPV has been reported in adults with CSU (11,18,20). Consistent with the literature, we also found high MPV value in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, this finding was consistent with that related to nonallergic inflammatory disease (23,24). In another study involving adult patients with CSU, MPV values in the patient group were reported to be higher than those in healthy controls (11). Our results regarding MPV were not consistent with the study involving children with CSU (15).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…[26] In a study by Topal et al [27] conducted on 128 preschool patients with allergic eczema, their PDW levels were lower than those in the control group, but the MPV levels were higher. In a study by Chandrashekar et al [28] carried out with 45 patients with chronic urticaria, both the MPV and PDW levels were significantly higher in the study group than they were in the control group and there was a correlation between the increase in disease severity and the increase in MPV and PDW levels. Patients with high PDW value in our study group also had high MPV values (p<0.05).…”
Section: Discussionmentioning
confidence: 89%